کوردستان لە نێوان هێڵی ئاسنی بەغداد – بەرلین 16 مارت 1889 و سایکس – بیکۆدا 16 ئایار 1916 - أمین, ته‌لار علی (Sulaimani Journal for Humanities, 2018)
ABSTCRAT Kurdistan Between Baghdad-Berlin Railroad, 16 March 1889, and Sykes- Picot, 16 May 1916 Kurdistan has always been in the center of forces conflicts, and in the colonialism competition, Kurdistan and middle-east was a base for supporting strategic depth for occupying power. This made this area a field for geopolitical effects among Caucasus- Caspian-Kurdistan-Gulf- East of Mediterranean, for the sake of road and energy. Between 16 March 1889 and 16 May 1916, Kurdistan and middle-east went into a dangerous stage due to oil wells, Germany came to the Middle East as a new capital force to 'Drang Nach Ostres' areas where the UK had its strategic depth. The UK was in historical conflict with Russia and France in order to control the area. Germany's intrusion was the UK's first fear, but the most fearful step was when the German teams arrived in Mosul state and especially to Kirkuk city seeking oil. After looking for oil, in a special report they mentioned the huge amount of oil that can be used for competition with Russian and US oil, on the condition of building a transpiration pipe or road. For this aim, Germany took the privilege from Osman Empire to build a Baghdad-Berlin railroad on 16 March 1889. This railroad joins Europe to Anatolia to the Gulf, as this area is considered as the heart of world trade and covered most of the world war places at the time. This line was a major factor for invading Mesopotamia when the oil advantage in Mesopotamia was achieved, this was the UK's first privilege. That was one of the most important factors for breaking up the war in the middle-east. From here, power balance started, Baghdad-Berlin railroad led to the gathering of UK-France-Russia in one side regardless of their conflicts. Thus, the conflicts and struggles for obtaining Kurdistan oil privilege at the Baghdad- Berlin railroad resulted in the division of Kurdistan at Sykes-Picot.